KREATIVITAS GURU BERSERTIFIKASI DALAM PEMANFAATAN MEDIA PEMBELAJARAN DI MADRASAH IBTIDAIYAH NEGERI (MIN) 2 BANDA ACEH (The Creativity of Certified Teacher in Utilizing Learning Media in Madrasah Ibtidaiyah Negeri (MIN) 2 Banda Aceh) - Ita Rahmadayani; Lailatussaadah Lailatussaadah; Cut Nya Dhin (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2021)
The quality of education is determined by teacher performance. While report shows that teacher performance is satisfactory, on the other hand, the quality of education in Aceh is desperate. The purpose of this study is to describe the creativity of certified teachers in utilizing learning media in MIN 2 Banda Aceh. The type of this research is qualitative and the subjects of this study were certified teachers and school principal. The data collection technique is through observation, interviews, and documentation. Data were analysed by Miles and Huberman's theory. The results of this research showed that there are four types of teacher creativities in utilizing learning media at MIN 2 Banda Aceh. First, fluency in thinking, teachers have the initiative in preparing learning media. Second, the flexibility of thinking, teachers use variety of learning medias in teaching. Third is originality, teachers’ innovation in preparing and using learning media. Fourth, elaboration, teachers and students collaborate in preparing learning media. The more creative the certified teacher in utilizing learning media, the more motivations in learning the students get. Thus, it improves student’s learning outcomes that contributes to the school quality and accreditation. Therefore, the teacher needs to be given further assistance so that the teacher can create and develop learning media with students, not only using the media that is already available.